The storage of indenical information across segmental length utterances - File-Murier, Richard J.; Turiciano, Samuel (Interacción, 2012)
This study examines the ability of listeners to store and recall indexical properties in segmental- length utterances, including details regarding the socially-constructed category “gender” as well as information about individual voices. The idea that indexical properties are irrelevant to speech recognition is a core assumption of generative phonological theory, which emphasizes the role of abstraction and categorization in identifying symbolic-like phonemic strings that are serially ordered. On the other hand, Pisoni (1997) and subsequent work have shown convincingly that this is not the case; indexical information is highly relevant and stored in lexical memory, evidenced by the fact that speakers recognize words uttered by familiar voices faster than unfamiliar voices. This study reports on a simple listening task, in which participants heard segmental-length stimuli (a-i-r-l-m-n-z-s) produced by both familiar and unfamiliar voices. Our results show that listeners store information regarding both gender classification and individual gestural behavior on utterances even as small as the segment. Higher correct identification scores are reported for the voiced sound /z/ than the voiceless /s/, indicating that listeners store information regarding individual speakers’ fundamental frequency and/or vocal cord physiology. At the same time, the identification scores for the voiceless sound /s/ was well above chance, indicating that listeners also store information regarding the configuration of individual speaker’s oral tracts. Our findings contribute to the growing body of research that phonological representation goes well beyond serially-ordered abstract symbols; it is rich and detailed (Pisoni, 1997; Port, 2010). At the same time, our results could also be taken as supportive of the Motor Theory of phonological representation, given that our results indicate storage of physiological differences and gestural properties of meaningless sounds (Galantucci et al., 2006). We also report an unexpected, albeit preliminary finding: Female listeners seem to recall more accurately acoustic detail regarding other female voices, as their identification scores for female stimuli were significantly higher than the scores achieved by male listeners.